Gender and Buddhist Doctrine - Alice Collett (St Andrews Encyclopaedia of Theology)
Women have been part of Buddhism since its inception in India, both as nuns and laity. As the tradition progressed, both within India and beyond, texts and traditions emerged that are or can be perceived as negative towards women. Within Buddhist texts, this negativity is shaped around two factors – the construction of a ‘female nature’ that is positioned as inferior, and expositions that identify sexual desire as something to be transcended (for those treading the path) that are or can be conflated as a problem with the female body (as a site of desire). This article will survey both of these issues from the perspective of Buddhist doctrine and Buddhist ethics (as I have begun to do elsewhere, see Collett 2018). Within this more comprehensive, encyclopaedic setting Buddhist doctrine and ethics are positioned more fully as the (obvious) starting point for analysis relating to gender issues. Hence, once more establishing that if we want to know what Buddhism says about gender we look to doctrine and ethics for the answer.